Linoleic acid and alpha linolenic acid ratio in poultry feed: A review (Research, Society and Development, 2021)
The use of lipids in poultry feed is a widely used nutritional strategy because it contributes to the energy increment, provides important nutrients for nutritional balance, and is the main source of polyunsaturated fatty acids. The polyunsaturated fatty acids comprise the families of omega-3 and omega-6 fatty acids. Where their main representatives are the linoleic, alpha-linolenic, arachidonic, and docosahexaenoic acids.  These acids have been widely studied due to their various functions in the body of breeding birds, such as the improvement of the chick quality, egg enrichment, anti-inflammatory function, fat reduction, among others. Due to these benefits, the enrichment of eggs with these acids has been sought through the manipulation of the diet. For this, several lipidic sources rich in n-3 PUFAs have been used, such as flaxseed, canola, and fish oils. This review aims to address the effect of different ratios of linoleic acid (18:2 n-6) and alpha linolenic acid (18:3 n-3) in the diet of laying birds. The methodology used was a descriptive study, based on published scientific articles, thus resulting in a data compilation for this literature review.